E-Presence Application Increases the Level of Health Personnel Discipline to Improve the Quality of Health Services in Hospitals (Systematic Review Paper) - Bambang Ilamto; Dewi Rokhmah; Dwi Prijatmoko; Wiwien Sugih Utami (Universitas Malahayati, 2024)
ABSTRACT In the era of increasingly advanced digital technology development, the government in Indonesia uses the E-presence digital attendance application to make attendance easier for its health workers. The use of e-presence is a form of progress in information technology in government. It is necessary to research changes in the level of discipline of health workers in implementing E-presence so that it can improve the quality of service or even reduce the quality of service. Find out how the use of E-presence among health workers can improve work discipline and improve service quality. The research design in this article uses descriptive qualitative research with data originating from the results of systematic reviews from various relevant national journal sources. Articles were obtained from Google Scholar and PubMed with identification in 2023 via Google Scholar n=205 and PubMed n=80. National and International Articles. With the keywords